A Strecker approach to 2-substituted ethyl 5-aminothiazole-4-carboxylates. Issue 16 (20th April 2016) - Cheng, Ken; McClory, Andrew; Walker, Whitney; Xu, Jie; Zhang, Haiming; Angelaud, Remy; Gosselin, Francis
Graphical abstract: Abstract: A general approach to 2-substituted ethyl 5-aminothiazole-4-carboxylates is reported herein. Both aliphatic and aromatic thioamides undergo 1, 2-addition to ethyl glyoxylate to give hemiaminals which, when treated with acetyl chloride, undergo elimination to the corresponding imines. Upon exposure to aqueous sodium cyanide the imines undergo a Strecker addition–cyclization reaction to provide the target heterocycles in modest to good yields over the 3-step process.